Cervical human papillomavirus infection and persistence: a clinic-based study in the countryside from South Brazil - Coser,Janaina (2016)
Abstract Human papillomavirus (HPV) infection is common in sexually active women and viral persistence may cause intraepithelial lesions and eventually progress to cervical cancer (CC). The present study aimed to investigate epidemiological factors related to HPV infection and to evaluate viral persistence and CC precursor lesions frequencies in women from a city in the countryside of South Brazil. Three hundred women were recruited from a primary public health care clinic. The patients were interviewed and underwent sampling with cervical brushes for HPV-DNA detection/typing by a PCR-based assay and cytological analysis by Pap smear test. HPV was detected in 47 (15.7%) women. HPV infection was significantly associated with young age (<30 years) and low socio-economic status. Seventeen (5.7%) women presented cytological abnormalities, three of them with precursor CC intraepithelial lesions. A subgroup of 79 women had been previously analyzed and thirteen (16.4%) were persistently infected, two with precursor CC intraepithelial lesions and high-risk HPV types infection (both of them without cervical abnormalities in the first exam). In conclusion, HPV infection was associated with young age (<30 years) and low family income; viral persistence was low (16.4%) but related to CC precursor lesions; and HPV-DNA high risk types detection would help to screen CC in the population.